Development and Optimization of Chromosomally-Integrated Fluorescent Mycobacterium tuberculosis Reporter Constructs - Kolbe, Katharina; Bell, Alice C.; Prosser, Gareth A.; Assmann, Maike; Yang, Hee-Jeong; Forbes, He Eun; Gallucci, Sophia; Mayer-Barber, Katrin D.; Boshoff, Helena I.; Barry III, Clifton E. (Frontiers in Microbiology, 2020)
Mycobacterium tuberculosis resides in the lungs in various lesion types with unique microenvironmental conditions. This diversity is in line with heterogeneous disease progression and divergent drug efficiency. Fluorescent reporter strains can be used to decipher the micromilieu and to guide future treatment regimens. Current reporters using replicating plasmids, however, are not suitable for long term mouse infections or studies in nonhuman primates. Using a combination of recombinant DNA and protein optimization techniques, we have developed reporter strains based on integrative plasmids, which exhibit stimulus-response characteristics and fluorescence intensities comparable to those based on replicating plasmids. We successfully applied the concepts by constructing a multi-color reporter strain able to detect simultaneous changes in environmental pH, Mg2+ concentrations, and protein expression levels.